High-Performance Hybrid White Organic Light-Emitting Diodes Utilizing a Mixed Interlayer as the Universal Carrier Switch - 丁磊 李怀坤 张麦丽 程君 张方辉 (Chinese physics letters, 2015)
A new interlayer is successfully used to be a universal carrier switch, developing high-performance hybrid white organic light-emitting diodes （WOLEDs）. By dint of this interlayer, the two-color hybrid WOLED shows a maximum total current efficiency （CE） and power efficiency （PE） of 48.1 cd/A and 37.6 Im/W, respectively, while the three-color hybrid WOLED shows a maximum total CE and PE of 33.8 cd/A and 25.7Im/W, respectively. The color rendering index of the three-color hybrid WOLEDs are ≥ 75, which is already a sufficient level for many commercial lighting applications. In addition, both the two-color and three-color hybrid WOLEDs show low efficiency roll-off and stable color. Furthermore, devices with the new interlayer show much higher performance than devices with the most commonly used 4,4-N,N-dicarbazolebiphenyl and N,N＇-di（naphthalene-l-yl）-N,N＇- diphenyl-benzidine interlayers.